Drapery in Exile: Edward III, Colchester and the Flemings, 1351–1367. Issue 338 (December 2014) - Lambert, Bart; Pajic, Milan
Abstract Throughout the fourteenth century, Edward III issued several letters of protection encouraging Flemish textile workers to establish their trade in England. During the centuries that followed, historians have disagreed about the newcomers' contribution to the development of the English drapery. Lacking in each debate were quantifiable data related to the presence of Flemish cloth‐workers on English soil. This article argues that, between 1351 and 1367, over 100 immigrants from the Low Countries settled in Colchester, twenty‐seven of whom were Flemish textile manufacturers exiled from Flanders and welcomed by Edward III in 1351. Attracted by excellent natural conditions for clothmaking, a shortage of manpower following the Black Death and an open economic environment, they made a vital contribution to the town's development as an internationally renowned centre of textile production that was able to withstand the pattern of urban decay so prevalent in other parts of late medieval England.